A dust-free lightweight gypsum self-leveling

Through hydrophobic modification of aggregates, dynamic network enhancer and white oil spraying technology, the problems of dust release, difficult to balance fluidity and mechanical properties, insufficient crack resistance and poor construction adaptability during construction are solved, and dust-free, efficient and uniform construction results are achieved.

CN119751011APending Publication Date: 2025-04-04HEBEI JIANGGONG NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411972714.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing gypsum self-leveling materials have problems in the construction of dust release, difficult to balance fluidity and mechanical properties, insufficient crack resistance and poor construction adaptability.

Method used

The surface hydrophobic modification technology of aggregate surface, dynamic network enhancer and white oil spraying process are used to modify the interface strength of aggregate and gypsum substrate, build a reversible physical network and reduce friction between particles, improve the material's fluidity, crack resistance and construction adaptability.

Benefits of technology

It has achieved dust-free construction, balanced improvement of fluidity and mechanical properties, significant enhancement of crack resistance and improvement of construction efficiency, and solved the shortcomings of traditional materials in these aspects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751011A_ABST
    Figure CN119751011A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a dust-free lightweight gypsum self-leveling, wherein the self-leveling gypsum comprises the following components in parts by weight: gypsum base material: 300-400 parts of semi-hydrated gypsum; 100-150 parts of α high-strength gypsum; lightweight aggregate: 150-200 parts of vitrified microspheres; 50-100 parts of expanded perlite, and also provides a preparation method of dust-free lightweight gypsum self-leveling, comprising the following steps: S1, performing hydrophobic modification on the aggregate to improve the bonding force between the aggregate and the base material; and at the same time, mixing and dissolving the liquid phase additive to form a uniformly distributed dynamic network reinforcement system; S2, adding the dry raw materials into a mixer and mixing them to form a uniform dry mix. The present invention improves the fluidity, crack resistance, construction adaptability and environmental protection performance of the material through the hydrophobic modification of the aggregate, the dynamic network reinforcement system and the white oil spraying technology, and meets the needs of modern construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a dust-free lightweight gypsum self-leveling. Background Art

[0002] In recent years, with the development of the construction industry, ground leveling, as a key link in decoration projects, has put forward higher requirements on the performance of materials. Gypsum self-leveling materials have gradually become an important choice in the construction industry due to their good fluidity, high construction efficiency and automatic leveling. This type of material can adaptively fill uneven areas on the ground through fluidity, reduce the complex operation of traditional manual leveling, and significantly improve construction efficiency and final ground quality.

[0003] Existing technologies have improved some of the properties of gypsum self-leveling materials through various methods. For example, some materials introduce chemical water reducers and enhancers to improve the fluidity of the slurry, thereby speeding up the laying speed and improving the flatness and compactness of the ground; in terms of crack resistance, by adding anti-crack fibers or optimizing the aggregate ratio, the material has a certain crack resistance after hardening.

[0004] However, the existing technology still has obvious shortcomings in actual use. The problem of dust release during construction has not been fundamentally solved. Relying solely on closed equipment or personal protective measures not only increases costs, but also limits the widespread application of materials. In terms of fluidity, the existing technology relies too much on the regulation of water-cement ratio or chemical water reducers, which makes it difficult to balance the fluidity and mechanical properties of the slurry. At the same time, stratification is common, affecting the uniformity and strength of the hardened material. In addition, the improvement of the material's crack resistance relies more on surface enhancement measures, lacks fundamental improvements in interface bonding strength and stress dispersion capabilities, and cracks are prone to propagate during the drying stage, affecting its service life. In terms of construction adaptability, the initial setting time of traditional gypsum self-leveling materials is too short to meet the needs of large-area paving, the fluidity decreases rapidly, and the leveling effect is poor. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a dust-free lightweight gypsum self-leveling material, which solves the problems of dust release, difficulty in balancing fluidity and mechanical properties, insufficient crack resistance and poor construction adaptability in the prior art.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a dust-free lightweight gypsum self-leveling, the self-leveling gypsum comprising the following components in parts by weight: Gypsum base material: hemihydrate gypsum: 300-400 parts; α high-strength gypsum: 100-150 parts; Hemihydrate gypsum generates dihydrate gypsum during the hydration process, which provides the basis for the setting and hardening of the material. Its reaction characteristics determine the fluidity and early strength of the material. This ratio can ensure the operability time and final hardening strength of the slurry during construction. α high-strength gypsum improves the compressive strength and flexural strength of the material by providing a high-density crystal structure, making up for the shortcoming of insufficient strength of hemihydrate gypsum after hardening. This ratio ensures the uniformity of the mechanical properties of the material after hardening, and will not increase the self-weight of the material or reduce its fluidity due to excessive dosage. Lightweight aggregate: vitrified microspheres: 150-200 parts; expanded perlite: 50-100 parts; The surface of lightweight aggregate is smooth and airtight, with high strength and low water absorption. It can enhance the overall strength and stability of the material while ensuring lightness. The reasonable distribution ensures uniform filling of aggregate and reduces the risk of slurry stratification and aggregate sinking. Expanded perlite has a porous structure and low density, which further reduces the overall density of the material. Its water absorption makes the slurry show good bonding performance during the curing process. However, the water absorption rate is effectively controlled by hydrophobic modified silane treatment, avoiding the reduction of slurry fluidity. Dynamic network enhancer: polyethylene glycol: 20-40 parts; polyvinyl alcohol: 10-20 parts; silane coupling agent: 5-10 parts; polyethylene glycol reduces the interfacial tension between particles, making the aggregate surface in the slurry uniformly wetted and avoiding the suspension of dust particles. At the same time, its molecular chain forms a reversible physical network in the slurry, improving the rheological resistance and self-healing property of the slurry during construction; after polyvinyl alcohol is dissolved in water, it can interact with other components through hydrogen bonding to form a dynamic physical network. During the construction process, the network provides temporary support to prevent aggregate sedimentation, and further enhances the crack resistance and toughness of the material after hardening; Silane coupling agent can establish a chemical bond between lightweight aggregate and gypsum substrate, significantly improving the interfacial bonding strength between aggregate and substrate. The use of silane coupling agent not only enhances the stability of the dynamic network, but also improves the mechanical properties of the final material; Interface regulator: nano magnesium silicate: 10-20 parts; hydrophobic modified silane: 5-10 parts; Nano magnesium silicate provides strong adsorption capacity, and enhances the adhesion between particles through physical adsorption and van der Waals force, thereby reducing particle dispersion and suspension. At the same time, the layered structure of nano magnesium silicate forms a microscopic support network in the slurry, improving the material's crack resistance. Hydrophobic modified silane reacts with the hydroxyl groups on the surface of the particles to form a hydrophobic protective layer. On the one hand, it improves the wettability of the particles and reduces dust dispersion; on the other hand, it enhances the water resistance of the material and prevents the performance of the cured material from degrading in a humid environment. Fluidity regulator: polycarboxylate water reducer: 2-5 parts; thickener: 2-5 parts; Polycarboxylate water reducer can reduce the viscosity of slurry, improve fluidity, avoid particle segregation and water bleeding, and maintain the uniformity of slurry; thickener has excellent hydration and water retention performance, and stabilizes the dispersion state between aggregate and slurry by forming a colloidal viscosity network, avoiding particle sedimentation and material stratification; Auxiliary additives: latex powder: 20-30 parts; white oil: 10-20 parts; retarder: 1-3 parts; Defoaming agent: 1-3 parts; Anti-cracking fiber: 0.5-1 part; As a flexibility enhancer, latex powder forms a uniform organic polymer network during the hydration process, which increases the material's anti-bending properties and improves the bonding strength with the base layer. White oil is evenly distributed on the particle surface through the spraying process, reducing the friction and electrostatic adsorption between particles, thereby significantly reducing dust release. Retarder is used to provide a reasonable construction window. Defoamer is used to eliminate bubbles in the slurry and improve the surface smoothness of the material after hardening. Finally, the addition of anti-cracking fiber can enhance the material's anti-cracking properties and avoid cracks caused by drying shrinkage. Preferably, the lightweight aggregate comprises: Vitrified microspheres, with a particle size of 10 to 150 microns, provide uniform particle distribution. In the slurry, the presence of vitrified microspheres effectively reduces the density of the material. At the same time, their smooth surface reduces the friction between particles and dust release, making the slurry show better fluidity and dust-free effect during construction; Expanded perlite, with a particle size of 50 to 200 microns. The expanded perlite with a particle size distribution of 50 to 200 microns has a moderate distribution and can form a uniform particle filling system with vitrified microspheres, while providing an additional lightweight effect; The surfaces of the vitrified microspheres and expanded perlite are treated with hydrophobic modified silane and then dried for use; the modified treatment can effectively improve the fluidity and stability of the slurry, and through the chemical bonding action of the silane coupling agent, the interfacial bonding strength between the vitrified microspheres and expanded perlite and the gypsum substrate is greatly improved, thereby avoiding the separation or shedding of aggregates during the hardening process of the slurry.

[0007] Preferably, the dynamic network enhancer comprises: Polyethylene glycol, with a molecular weight of 4000 to 6000, PEG with a molecular weight of 4000 to 6000 has a suitable chain length and can form a reversible physical network in the slurry system through the flexibility of the molecular chain; Polyvinyl alcohol, alcoholysis degree is 87% to 98%, and polymerization degree is 1700 to 2000. PVA with alcoholysis degree of 87% to 98% has moderate water solubility, while the polymerization degree of 1700 to 2000 enables it to provide higher molecular chain strength and toughness; Silane coupling agent is KH-1720 silane. KH-1720 silane is a bifunctional compound. The siloxane group at one end can react with the hydroxyl group on the surface of the aggregate to form a strong chemical bond; the organic group at the other end can form an interface bond with the gypsum substrate or polymer material.

[0008] Preferably, the interface regulator comprises: Nano magnesium silicate, particle size is 20-50 nanometers, specific surface area is 200-300m 2 / g, the layered structure and high specific surface area of ​​nano magnesium silicate enable it to enhance the binding force between particles through physical adsorption and van der Waals force. In the slurry, nano magnesium silicate is distributed on the surface of the particles to form an adsorption layer, which significantly reduces the free movement of the particles and thus inhibits the release of dust; the particle size of nano magnesium silicate enables it to fill the microscopic gaps between the particles and form a uniform microscopic support network, which can improve the fluidity and uniformity of the slurry, and at the same time enhance the density and strength of the material during the hardening stage; The hydrophobically modified silane is used in an amount of 0.5% to 1% of the weight of the aggregate. The hydrophobically modified silane is a bifunctional compound, one end of which can combine with the hydroxyl group on the surface of the lightweight aggregate to form a strong chemical bond; the other end can form a hydrophobic protective layer; preferably, the fluidity regulator includes: Polycarboxylate water reducer, the main chain structure is polyether type, the molecular weight is 20000-30000, the molecular chain of polycarboxylate water reducer with a molecular weight of 20000-30000 is relatively long, and it can form a stable dispersion system in the slurry, thereby significantly reducing the viscosity of the slurry and improving fluidity; Thickener, with a viscosity of 2000-4000 mPa·s and a particle size of less than 100 microns, forms a uniform network structure through its high viscosity, stabilizes the aggregate and gypsum substrate particles in the slurry, makes their distribution more uniform, and avoids the sedimentation of aggregates under gravity. Thickeners with a particle size of less than 100 microns can disperse rapidly in the slurry, further enhancing the slurry's anti-stratification performance while ensuring that fluidity is not excessively affected; Preferably, the auxiliary additives include: Latex powder, with a particle size of 50 to 200 microns, is designed to fill the gaps between particles in the slurry system and enhance the fluidity and uniformity of the slurry; White oil is No. 100 mineral oil. Its lubricating effect reduces the viscous resistance between particles inside the slurry, further improving the flowability of the slurry and making the construction smoother. The retarder is sodium citrate; sodium citrate combines with calcium ions in gypsum through complexation, reducing the activity of calcium ions, delaying the hydration process of gypsum, thereby extending the initial setting time and providing a sufficient construction window; The defoaming agent is a polyether-modified silicone oil; the polyether-modified silicone oil defoaming agent has good surface activity. After acting on the surface of the bubbles in the slurry, it can reduce the surface tension of the bubbles, causing the bubbles to burst quickly and release gas.

[0009] The present invention also provides a method for preparing dust-free lightweight gypsum self-leveling, comprising the following steps: S1. The aggregate is subjected to hydrophobic modification treatment to improve the bonding strength between the aggregate and the substrate; at the same time, the liquid phase additive is mixed and dissolved to form a uniformly distributed dynamic network reinforcement system; The hydrophobic modification of aggregate reduces its water absorption, effectively preventing water loss during the hydration process of the slurry. At the same time, the dynamic network enhancement system improves the wettability and dispersibility between particles through molecular cross-linking, fundamentally improving the uniformity and fluidity of the slurry; S2, adding the dry raw materials into a mixer and mixing to form a uniform dry blend; Through uniform stirring, the modified aggregate and gypsum matrix can form a stable mixed system, ensuring that there is no particle agglomeration when the subsequent liquid phase is added. At the same time, the high specific surface area and layered structure of nano magnesium silicate effectively enhance the interfacial bonding force of the slurry and improve the crack resistance of the material; S3. Slowly add the liquid phase additive to the dry mix, and add latex powder and retarder at the same time to further enhance fluidity and construction adaptability; Through the gradual fusion of the liquid phase and the dry mix, the particle distribution of the slurry is more uniform, avoiding the settlement and stratification of aggregates. At the same time, the retarder provides the initial setting time, ensuring a smooth construction process and reducing rework and quality problems. S4. Spray white oil through a spraying device during the stirring process to reduce dust and improve particle lubricity. The spraying pressure is 4-6 MPa and the spraying time is 3-5 minutes. White oil spraying technology reduces dust emissions while improving the construction performance of the material, making the slurry flow smoother and more uniform, greatly improving construction efficiency, and making the construction environment more environmentally friendly and healthy; S5. Spread the evenly stirred slurry onto the construction surface to fill the uneven surface and achieve a self-leveling effect. The initial setting time is 25 to 40 minutes. The slurry will automatically level after laying, without the need for additional manual intervention, making construction more efficient. The initial setting time is stable, ensuring the time window for construction. The surface flatness and mechanical properties of the material are better than those of traditional products. S6. Wet curing is performed on the completed surface to ensure the strength and stability of the material. The curing temperature is 20-30°C, the humidity is 50%-70%, and the curing time is 48 hours; Wet curing ensures the mechanical properties and surface quality of the material, significantly reduces the risk of crack formation during the drying process, and improves the final construction effect.

[0010] Preferably, the S1 comprises: The vitrified microspheres and expanded perlite were subjected to hydrophobic modification using KH-560 silane at a modification temperature of 50-70°C for 2-4 hours; Dry the modified aggregate at a temperature of 50 to 60°C for 2 to 3 hours; Polyethylene glycol and polyvinyl alcohol are dissolved in warm water at a weight ratio of 1:1 to 2:1, the dissolution temperature is 50 to 60° C., and the stirring time is 5 to 10 minutes to prepare a uniform liquid phase mixture.

[0011] Preferably, S2 includes: Add hemihydrate gypsum, α high-strength gypsum, vitrified microspheres, expanded perlite and nano magnesium silicate into a dry mixer in proportion. Through a reasonable raw material ratio and adding sequence, ensure that the components are evenly distributed during the mixing process to avoid the sedimentation or floating of lightweight aggregates, and at the same time enhance the interface bonding performance between the substrate and the aggregate; The stirring speed is 200-500 rpm; The stirring time is 3 to 5 minutes; During the mixing process, the particles should be evenly distributed to avoid aggregate separation. During the mixing process, the equipment should maintain a constant speed to reduce the uneven distribution of particles. The mixing time should be controlled within 3 to 5 minutes to ensure full contact and mixing between particles, but avoid aggregate separation or wear of the modified layer caused by too long mixing; After the dry mixing is completed, the mixture is left to stand for use in subsequent liquid phase mixing operations. The standing process improves the stability of the mixture, lays a foundation for uniform distribution for subsequent liquid phase addition, and ensures that the dispersion of the particles and the integrity of the modified layer are not damaged.

[0012] Preferably, S3 includes: Slowly add the liquid mixture to the dry mix at a rate of 100-200 mL / min to prevent uneven mixing. Slow liquid addition ensures uniform dispersion of the slurry, avoids particle agglomeration and stratification, and improves fluidity and construction adaptability. While adding the liquid phase mixture, latex powder, retarder and defoamer are added in sequence. The sequential addition of latex powder, retarder and defoamer improves the flexibility of the slurry, prolongs the construction time and improves the density after hardening, providing a guarantee for the final construction effect; The stirring speed of wet mixing is 300-600 rpm, and the stirring time is 5-8 minutes; During the wet mixing process, white oil is sprayed through high-pressure spraying equipment with a spraying pressure of 4 to 6 MPa and a spraying time of 3 to 5 minutes to further reduce dust generation; wet mixing combined with white oil spraying technology makes the slurry more uniform and fine, and the particle fluidity is significantly enhanced. At the same time, dust release is greatly reduced, and the construction environment friendliness is significantly improved.

[0013] The present invention provides a dust-free lightweight gypsum self-leveling material, which has the following beneficial effects: 1. The present invention adopts the technology of aggregate surface hydrophobic modification. By using KH-560 silane to modify the vitrified microspheres and expanded perlite, the water absorption rate of the aggregate is significantly reduced, and the interface bonding force between the aggregate and the gypsum substrate is enhanced. Compared with the problems of high water absorption rate and weak interface bonding force of untreated aggregate in the prior art, this technical solution solves the problems of uneven slurry hydration, material stratification and unstable mechanical properties after hardening.

[0014] 2. The present invention innovatively introduces a dynamic network enhancement system, utilizes the synergistic effect of polyethylene glycol and polyvinyl alcohol, constructs a reversible physical network, and improves the fluidity and anti-sedimentation ability of the slurry. Compared with the traditional technology that simply relies on water reducers to improve fluidity, the present invention not only optimizes the particle dispersibility, but also effectively avoids the problems of particle stratification and slurry segregation, and the construction effect is more uniform and smooth.

[0015] 3. The present invention forms a lubricating layer on the surface of the particles through the white oil spraying process, which effectively reduces the friction and electrostatic adsorption between the particles and significantly inhibits the release of dust. Compared with the traditional technology that requires a closed construction environment or wearing protective equipment to reduce dust, the present invention completely solves the problem that dust-free construction is difficult to achieve from the essence of the material. The construction environment is cleaner and the health risks are greatly reduced.

[0016] 4. The present invention uses a retarder to scientifically control the setting time, extending the initial setting time to 25 to 40 minutes, fully ensuring the construction operation window. Compared with the prior art solutions that cause construction inconvenience and material hardening defects due to too fast setting, the present invention effectively avoids the problems of decreased fluidity and reduced construction efficiency caused by rapid setting, while ensuring the uniformity and strength of the hardened material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Please see attached Figure 1 : Example 1: Standardized dust-free lightweight gypsum self-leveling preparation process Material preparation Weigh 200 parts of vitrified microspheres and 100 parts of expanded perlite. Add the aggregates to a 0.8% concentration of KH-560 silane solution and stir evenly. The modification temperature is controlled at 60°C and the time is set to 3 hours. After the modification is completed, put the aggregates into a drying oven, set the temperature to 55°C, and the drying time is 2.5 hours.

[0020] At the same time, 40 parts of polyethylene glycol (PEG, molecular weight 5000) and 20 parts of polyvinyl alcohol (PVA, alcoholysis degree 90%, polymerization degree 1800) were weighed and mixed in a weight ratio of 2:1, and then added into warm water at 55°C and stirred for 8 minutes until a transparent and uniform liquid mixture was formed.

[0021] Dry Mix Raw Materials 350 parts of hemihydrate gypsum, 120 parts of α-high-strength gypsum, modified vitrified microspheres and expanded perlite were added to a dry mixer. Then 15 parts of nano magnesium silicate (particle size 30 nanometers, specific surface area 250 m 2 / g), the stirrer speed was adjusted to 400 rpm, and the mixing time was controlled to 4 minutes to ensure that the raw materials were mixed evenly.

[0022] Liquid and wet mixing The prepared liquid phase dynamic network mixture was slowly poured into the dry mix at a liquid addition rate of 150 mL / min. Then 25 parts of latex powder, 1.5 parts of retarder (sodium citrate), and 1 part of defoamer (polyether-modified silicone oil) were added, and the wet mixing speed was set to 500 rpm for 6 minutes.

[0023] White oil spraying During the wet mixing process, 15 parts of No. 100 white oil were sprayed into the slurry through a high-pressure spraying device. The spraying pressure was set to 5 MPa and the spraying time was 4 minutes to ensure that the white oil was evenly distributed on the particle surface.

[0024] Slurry laying and maintenance Pour the prepared slurry onto the construction surface and spread it naturally to the low-lying area. It was observed that the slurry flow diameter was 300mm, without stratification or segregation. The initial setting time was 35 minutes. After paving, wet curing was carried out, and the curing conditions were 25℃, 65% humidity, and the curing time was 48 hours.

[0025] Effect verification After hardening, the material has a compressive strength of 20MPa, a flexural strength of 6MPa, and a dust release rate of less than 0.5%. Dust is almost invisible at the construction site, and the environmental cleanliness is significantly improved.

[0026] Example 2: Preparation process of fast-construction dust-free lightweight gypsum self-leveling Material Handling Select 150 parts of vitrified microspheres with a particle size of 20 to 100 microns and 50 parts of expanded perlite. Add the aggregate to a 0.6% concentration of KH-560 silane solution and stir for 2 hours at 50°C. After the modification is completed, place it at 55°C for drying for 3 hours. Weigh 30 parts of polyethylene glycol (molecular weight 4000) and 15 parts of polyvinyl alcohol (alcoholysis degree 95%, polymerization degree 1700), add them to 60°C warm water at a weight ratio of 2:1, and stir for 5 minutes to form a liquid mixture.

[0027] Dry Mixing Weigh 320 parts of hemihydrate gypsum, 100 parts of α high-strength gypsum, and 10 parts of nano magnesium silicate (particle size 25 nanometers, specific surface area 230m 2 / g). These raw materials and modified aggregate were added into dry mixing equipment and stirred for 3 minutes at a speed of 300 rpm.

[0028] Liquid phase addition and wet mixing Slowly add the liquid phase dynamic network mixture to the dry mix. Then add 20 parts of latex powder, 1.2 parts of retarder and 0.8 parts of defoamer. Adjust the mixer speed to 600 rpm and wet mix for 5 minutes until the slurry has uniform fluidity.

[0029] White oil spraying During the wet mixing process, 12 parts of white oil were evenly sprayed into the slurry through a spraying device with a spraying pressure of 4 MPa for 3 minutes to ensure that the particle surface was fully lubricated.

[0030] Construction and maintenance After the slurry is laid on the construction surface, it will automatically level. The initial setting time is about 30 minutes, which is suitable for rapid construction needs. The curing conditions are 22℃, 60% humidity, and 48 hours.

[0031] Effect verification After hardening, the compressive strength is 18MPa and the flexural strength is 5.5MPa. There is no water seepage during slurry laying, and the dust concentration in the construction area is less than 0.5%, which meets the requirements of rapid construction and environmental protection.

[0032] Example 3: Preparation process of high-strength dust-free lightweight gypsum self-leveling 200 parts of aggregate hydrophobically modified vitrified microspheres and 100 parts of expanded perlite were added to a 0.9% concentration of KH-560 silane solution, and stirred at 70°C for 4 hours. The aggregate was then dried at 60°C for 3 hours to ensure the stability of the modified layer.

[0033] Dynamic network liquid phase preparation Take 40 parts of polyethylene glycol (molecular weight 6000) and 20 parts of polyvinyl alcohol (alcoholysis degree 87%, polymerization degree 2000), add them into 55°C warm water in a weight ratio of 2:1, and stir for 10 minutes to form a dynamic network liquid phase.

[0034] Dry Mixing 400 parts of hemihydrate gypsum, 150 parts of α high-strength gypsum, modified aggregate and 15 parts of nano magnesium silicate (particle size 30 nanometers, specific surface area 300m 2 / g) was added into the dry mixing equipment and stirred for 5 minutes at a speed of 500 rpm to ensure uniform distribution of the raw materials.

[0035] Liquid phase addition and wet mixing Slowly add the dynamic network liquid phase, and at the same time add 30 parts of latex powder, 1.8 parts of retarder, and 1.2 parts of defoamer. The wet mixing time is 7 minutes, and the speed is adjusted to 500 rpm.

[0036] White oil spraying When wet mixing, spray 18 parts of white oil at a spraying pressure of 6MPa for 4 minutes to ensure uniform lubrication.

[0037] Construction and maintenance The slurry is poured into the construction surface, the initial setting time is 40 minutes, and the surface is automatically leveled. The curing conditions are 30℃, 70% humidity, and the curing time is 48 hours.

[0038] Effect verification After hardening, the compressive strength reaches 25MPa, the flexural strength reaches 8MPa, and the dust release rate is less than 0.4%. The material has outstanding performance and is suitable for high-load environments.

[0039] Example 4: Highly efficient dust suppression type dust-free lightweight gypsum self-leveling Aggregate handling and liquid preparation 180 parts of vitrified microspheres and 80 parts of expanded perlite were added to a 0.7% concentration of KH-560 silane solution, treated at 60°C for 3 hours and dried for 2 hours. The dynamic network liquid phase was prepared by dissolving 35 parts of polyethylene glycol (molecular weight 4500) and 17 parts of polyvinyl alcohol (degree of polymerization 1900) in 50°C warm water and stirring for 7 minutes.

[0040] Dry mix vs. wet mix The dry-mixed raw materials are 360 ​​parts of hemihydrate gypsum, 130 parts of α high-strength gypsum, and 12 parts of nano-magnesium silicate. The mixing time is 4 minutes, the rotation speed is 400 rpm, and the wet mixing time is 6 minutes after the liquid phase is added. During the wet mixing, 25 parts of latex powder, 1.5 parts of retarder and 1 part of defoamer are added.

[0041] White oil spraying and laying The spraying equipment sprays 15 parts of white oil on the slurry at a pressure of 5 MPa for 4 minutes. The initial setting time of the slurry after laying is 35 minutes.

[0042] Effect verification The dust release rate is reduced to 0.3%, and the slurry construction has good fluidity (flow diameter 310mm). The compressive strength is 20MPa and the flexural strength is 6MPa.

[0043] Example 5: Low temperature curing type dust-free lightweight gypsum self-leveling Materials and processing 150 parts of vitrified microspheres and 50 parts of expanded perlite were added to 0.8% KH-560 silane solution and stirred at 50°C for 2 hours. The drying temperature was set at 50°C and the drying time was 2 hours.

[0044] Liquid Phase and Stirring The dynamic network liquid phase was prepared by dissolving 40 parts of PEG (molecular weight 5000) and 20 parts of PVA (alcoholysis degree 88%) and stirring for 5 minutes. 340 parts of hemihydrate gypsum, 120 parts of α high-strength gypsum, modified aggregate and 10 parts of nano magnesium silicate were dry mixed for 3 minutes, and then the liquid phase was added and wet mixed for 6 minutes.

[0045] White oil spraying and laying Spray 12 parts of white oil, pressure 4MPa, spray time 3 minutes. The initial setting time of the slurry after laying is 30 minutes. The curing conditions are 20℃, humidity 60%, and curing time 48 hours.

[0046] Effect verification After curing and hardening under low temperature conditions, the compressive strength is 18MPa, the flexural strength is 5MPa, and the construction dust concentration is extremely low, meeting the environmental protection requirements of indoor construction.

[0047] Comparative Example 1: Preparation without hydrophobic modification of aggregate Corresponding embodiment: Embodiment 1 Aggregate handling No KH-560 silane modification was performed. 200 parts of vitrified microspheres and 100 parts of expanded perlite were used directly without changing their original water absorption. The aggregate was not hydrophobically modified and was directly used in the subsequent steps.

[0048] Dry Mixing As in Example 1, untreated vitrified microspheres, expanded perlite, 350 parts of hemihydrate gypsum, and 120 parts of α high-strength gypsum were added. and 15 parts of nano magnesium silicate were added into the dry mixing equipment. The stirring speed of the stirrer was set to 400 rpm and the stirring time was 4 minutes.

[0049] Liquid phase preparation and wet mixing The preparation of the dynamic network enhancer was consistent with Example 1, PEG and PVA were dissolved in a ratio of 2:1 and then added to the dry mix. At the same time, latex powder, retarder and defoamer were added, and the wet mixing time was 6 minutes.

[0050] White oil spraying and construction The same as in Example 1, 15 parts of white oil were sprayed, the spraying pressure was 5 MPa, and the time was 4 minutes. The slurry was directly laid, and the initial setting time was the same.

[0051] Comparative Example 2: No dynamic network enhancement system is used Corresponding embodiment: Embodiment 2 Aggregate handling The aggregate was modified using the modification process of Example 2, that is, 150 parts of vitrified microspheres and 50 parts of expanded perlite were treated with 0.6% KH-560 silane solution at a temperature of 50° C. for 2 hours and a drying temperature of 55° C. for 3 hours.

[0052] Exclusion of Dynamic Network Enhancement System The liquid phase preparation step of the dynamic network enhancement system was eliminated, and the addition of PEG and PVA was directly skipped.

[0053] Dry Mixing The modified vitrified microspheres and expanded perlite were dry-mixed with 320 parts of hemihydrate gypsum, 100 parts of α high-strength gypsum, and 10 parts of nano magnesium silicate. The mixer speed was 300 rpm and the mixing time was 3 minutes.

[0054] Liquid phase and wet mixing Skip the addition of the dynamic network liquid phase and only add 20 parts of latex powder, 1.2 parts of retarder and 0.8 parts of defoamer. Wet mix at a speed of 600 rpm for 5 minutes.

[0055] White oil spraying and construction The same as in Example 2, 12 parts of white oil were sprayed, the spraying pressure was 4 MPa, and the spraying time was 3 minutes. After the slurry was laid, the construction fluidity was observed.

[0056] Comparative Example 3: Cancelling the white oil spraying process Corresponding embodiment: Embodiment 3 Aggregate handling and liquid preparation Aggregate treatment and liquid phase preparation were performed completely according to Example 3. 200 parts of vitrified microspheres and 100 parts of expanded perlite were modified with 0.9% KH-560 silane solution for 4 hours and dried at 60° C. for 3 hours. The dynamic network reinforcement system was prepared according to the ratio of Example 3, with a ratio of PEG to PVA of 2:1.

[0057] Dry mixing and wet mixing Dry mixing steps: 400 parts of hemihydrate gypsum, 150 parts of α high-strength gypsum, 15 parts of nano magnesium silicate, and modified aggregate are added to the mixer, and the mixing time is 5 minutes at a speed of 500rpm. During wet mixing, dynamic network liquid phase, 30 parts of latex powder, 1.8 parts of retarder, and 1.2 parts of defoamer are added, and the wet mixing time is 7 minutes at a speed of 500rpm.

[0058] Cancel white oil spraying The white oil spraying process is eliminated and the slurry directly enters the laying step.

[0059] Construction and maintenance The initial setting time after slurry laying is 40 minutes, and the curing conditions are the same as those in Example 3.

[0060] Comparative Example 4: Aggregate particle size does not meet the requirements Corresponding embodiment: Embodiment 4 Aggregate handling 180 parts of vitrified microspheres with a particle size of 200-300 microns and 80 parts of expanded perlite with a particle size of 300-400 microns were selected. The aggregate was treated with 0.7% KH-560 silane solution, stirred at 60°C for 3 hours, and dried at 55°C for 2 hours.

[0061] Dry mixing and wet mixing Dry mixing: Mix the modified aggregate with 360 parts of hemihydrate gypsum, 130 parts of α high-strength gypsum, and 12 parts of nano magnesium silicate, stirring for 4 minutes at a speed of 400 rpm. Wet mixing: Prepare the dynamic network liquid phase according to Example 4, add the dry mix, and add 25 parts of latex powder, 1.5 parts of retarder, and 1 part of defoamer. Wet mixing time is 6 minutes.

[0062] White oil spraying and construction The white oil spraying was the same as in Example 4, with 15 parts sprayed, a pressure of 5 MPa, and a spraying time of 4 minutes.

[0063] Construction and maintenance The initial setting time after slurry laying is 35 minutes, and the curing conditions are the same as those in Example 4.

[0064] Comparative Example 5: Elimination of retarder Corresponding embodiment: Embodiment 5 Aggregate handling and liquid phase preparation Consistent with Example 5, 150 parts of vitrified microspheres and 50 parts of expanded perlite were treated with 0.8% KH-560 silane solution, stirred at 50°C for 2 hours, and dried at 50°C for 2 hours. The dynamic network enhancement liquid phase was prepared by dissolving 40 parts of PEG (molecular weight 5000) and 20 parts of PVA (degree of alcoholysis 88%) in 55°C warm water and stirring for 5 minutes.

[0065] Dry mixing and wet mixing Dry mixing: Mix the modified aggregate with 340 parts of hemihydrate gypsum, 120 parts of α high-strength gypsum, and 10 parts of nano-magnesium silicate, stirring for 3 minutes at a speed of 400 rpm. Wet mixing: Add dynamic network liquid phase, 25 parts of latex powder and 1 part of defoaming agent, but eliminate the retarder.

[0066] White oil spraying and construction The white oil spraying was the same as in Example 5, with 12 parts sprayed, a pressure of 4 MPa, and a spraying time of 3 minutes.

[0067] Construction and maintenance The initial setting time of the slurry after laying is 15 minutes (without the effect of retarder). The curing conditions are the same as those in Example 5.

[0068] Experiment 1: Slurry fluidity test Experimental procedures Sample preparation Slurry samples were prepared respectively using the formulas of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, Comparative Example 3. The slurry was stirred according to the respective process steps and maintained at an ambient temperature of 25° C. and a humidity of 60%.

[0069] After stirring, the slurry was allowed to stand for 1 minute to eliminate air bubble interference, and then the flowability test was started.

[0070] Liquidity test The slurry is poured into a standard flow test mold. The mold is placed on a horizontal flow table.

[0071] After removing the mold, observe the natural flow of the slurry under the action of gravity. Use a steel ruler to record the maximum flow diameter of the slurry in two vertical directions, and take the average value as the flow diameter of the sample.

[0072] Each group of samples was tested three times, and the results were recorded and averaged.

[0073] Experimental setup Environmental conditions: temperature 25°C, humidity 60%.

[0074] Evaluation index: flow diameter (mm). The better the fluidity, the larger the diameter. 280mm is the lower limit standard for excellent construction fluidity.

[0075] Test data of slurry fluidity of different samples The fluidity of the slurry depends on the dispersion and wettability of the particles in the material, which are affected by the dynamic network reinforcement system, the hydrophobic modification of the aggregate and the white oil spraying. The fluidity of Example 3 is the best, with an average flow diameter of 311.7 mm, which is significantly better than all the comparative samples. This shows the synergistic effect of multiple innovative technical solutions in improving fluidity performance; For Comparative Example 1 in which the aggregate was not hydrophobically modified, the flow diameter was only 221.3 mm. This difference was directly related to the water absorption of the aggregate. The unmodified vitrified microspheres and expanded perlite absorbed the free water in the slurry, weakening the fluidity of the slurry, while the hydrophobically modified aggregate provided a more stable interface bonding in the slurry, preventing excessive absorption of water, and significantly improving the fluidity. The flow diameter of the sample of Comparative Example 2 without the dynamic network reinforcement system was only 249 mm, which was significantly weaker than that of Examples 2 and 3. The PEG and PVA in the dynamic network reinforcement system improved the wettability of the particle surface and the dispersibility of the slurry by forming a molecular chain cross-linking network. At the same time, the flexibility of the molecular chain enhanced the resistance of the slurry during flow, thereby significantly improving the fluidity. The introduction of white oil spraying directly improves the lubricity of the particles and reduces the friction between the particles. After the white oil spraying is cancelled in Comparative Example 3, the fluidity is only 265.7 mm, indicating that there is a lack of an effective lubrication layer on the surface of the particles. The uniform coverage of white oil in Example 3 reduces the viscous resistance between the particles and makes the slurry flow more smoothly. This effect is particularly evident in the test of the flow diameter and is an important reason for improving the workability of the slurry.

[0076] Experiment 2: Dust release rate test Experimental procedures The experimental device is prepared to use a closed dust sampling box with a volume of 2 cubic meters and equipped with a laser dust concentration meter. The accuracy of the sampler is 0.01mg / m 3 The mixer was placed in the center of the box and the stirring speed was set to 300 rpm.

[0077] Sample preparation The slurry samples were prepared according to the formulas of Example 1, Example 3, Example 5 and Comparative Example 1 and Comparative Example 3. All samples were stirred under the same environmental conditions. Each sample was repeated 3 times to ensure the reliability of the data.

[0078] Experimental Procedure Weigh the sample: Take the same mass of slurry (2kg) and put it into the mixer.

[0079] Stir and measure: Start the mixer and stir continuously for 3 minutes. The laser dust measuring instrument will simultaneously record the dust concentration in the air during the stirring process. The data will be recorded every 5 seconds and the average value will be taken at the end.

[0080] Clean and Repeat: Clean the dust box after mixing is completed and repeat the test three times.

[0081] Experimental conditions Ambient temperature: 25℃, humidity: 60%.

[0082] Test samples: Example 1 (full process optimization), Example 3 (full optimization + high white oil content), Example 5 (optimization + low temperature curing); Comparative Example 1 (no hydrophobic modification), Comparative Example 3 (no white oil spraying).

[0083] Test results of dust concentration during mixing of different sample slurries The generation and release of dust during the slurry stirring process are closely related to the wettability, water absorption and friction characteristics of the particle surface. The dust concentrations of Examples 1 and 3 are both lower than 0.5 mg / m 3 , especially in Example 3, the dust concentration is even lower, only 0.31 mg / m 3 This shows that the dual optimization of hydrophobic modification and white oil spraying has a significant effect on improving dust-free performance. In contrast, the dust concentration of Comparative Example 1 is as high as 1.29 mg / m 3 , which directly reflects that the unmodified aggregates do not absorb enough water in the slurry, the particles are in frequent contact with the air, and dust is easy to generate and spread; For Comparative Example 3 without white oil spraying, the dust concentration is 0.92 mg / m 3 This result shows that the friction between particles increases after the lubricating layer is missing, the electrostatic adsorption effect is significant, and the particles are easy to separate from the slurry to form dust during the stirring process. In Examples 1 and 3, the spraying of white oil forms an effective lubricating layer on the surface of the particles, reducing the friction and static electricity between the particles and significantly reducing the dust release.

[0084] Experiment 3: Mechanical properties test (compressive and flexural strength) Experimental procedures Sample preparation According to the formulas of Example 1, Example 2, Example 3, Example 5 and Comparative Example 1, Comparative Example 2 and Comparative Example 4, slurry was prepared, stirred evenly and poured into a cubic mold (side length 40 mm).

[0085] Three specimens were made for each group of samples to ensure test repeatability. The stirring and molding conditions were kept consistent and the samples were left to stand at room temperature for 1 hour after molding.

[0086] Sample maintenance The specimens were cured for 48 hours at a humidity of 60% and a temperature of 25°C to ensure that the material was fully hardened. After the curing was completed, the specimens were removed and the surface was wiped with a damp cloth to remove attached dust or impurities.

[0087] Compressive strength test Place the sample in a pressure testing machine and set the loading speed to 2MPa / s until the sample fails and record the maximum bearing pressure. Take 3 samples from each group and calculate the average compressive strength.

[0088] Flexural strength test The specimens were subjected to three-point bending tests, and the maximum load-bearing capacity when the specimens broke was recorded. The flexural strength was calculated using a formula, and the test method was based on the standard building material mechanical properties test specifications.

[0089] Experimental conditions Temperature: 25℃; Humidity: 60%.

[0090] Test samples: Example 1, Example 2, Example 3, Example 5; Comparative Example 1 (no hydrophobic modification), Comparative Example 2 (no dynamic network reinforcement system), Comparative Example 4 (aggregate particle size does not meet the requirements).

[0091] Compressive and flexural strength test results of different samples The compressive strength and flexural strength directly reflect the mechanical properties of the material, especially the uniformity of aggregate distribution and the interfacial bonding between particles and substrates. The compressive strength of Example 3 reached 24.4MPa and the flexural strength reached 7.7MPa, far exceeding other samples. This shows that the synergistic effect of the dynamic network reinforcement system and the hydrophobic modification treatment not only improves the bonding between the substrate and the aggregate, but also enhances the overall structural density of the material. In Comparative Example 1, since the aggregate was not hydrophobically modified, the water absorption of the aggregate led to uneven hydration reaction of the slurry and insufficient interfacial bonding, which ultimately greatly reduced the strength, with a compressive strength of only 14.1MPa and a flexural strength of only 4.0MPa. Comparative Example 2, which does not introduce the dynamic network reinforcement system, also has poor mechanical properties, with a compressive strength of only 15.2 MPa. The physical cross-linked network of PEG and PVA can provide flexible support between particles and fill the microscopic gaps of the substrate, significantly improving the uniformity and crack resistance of the material. In Comparative Example 2, the lack of this flexible connection between particles leads to microscopic cracks after the slurry hardens, resulting in a decrease in strength. This dynamic network enhancement of mechanical properties is particularly evident in Examples 1 and 3.

[0092] Comparative Example 4, in which the aggregate particle size design is unreasonable, has a compressive strength of 16.8MPa and a flexural strength of 5.2MPa, which is slightly better than Comparative Examples 1 and 2, but still significantly lower than the embodiment. The presence of large-size aggregate leads to interfacial stress concentration, and the hydration products of the substrate are unevenly distributed, which ultimately weakens the strength of the material. In the embodiment, the reasonable aggregate particle size design is coordinated with the filling effect of nano-magnesium silicate, so that the material shows good interfacial bonding force and bearing capacity after hardening, thereby improving the overall strength. These comparative data fully illustrate the importance of innovative technical solutions in material performance optimization.

[0093] Experiment 4: Crack resistance test Experimental procedures Sample preparation Slurry was prepared according to the formulas of Example 1, Example 3, Example 5 and Comparative Example 2 and Comparative Example 4.

[0094] Prepare rectangular thin plate specimens with a thickness of 10 mm, a width of 50 mm, and a length of 200 mm. Make sure to make 3 specimens for each formulation to avoid errors.

[0095] Maintenance and treatment Place the specimen in an environment with a humidity of 60% and a temperature of 25°C for 48 hours. Take it out after the material is fully hardened.

[0096] After curing, each group of specimens was transferred to a drying oven at 60°C and dried for 24 hours to simulate the drying shrinkage process of the material.

[0097] Crack measurement After drying, the specimens were taken out and the number of surface cracks and the maximum crack length were measured using a high-precision crack tester.

[0098] Each group of specimens was measured three times, and the average values ​​of the crack number and crack length were recorded.

[0099] Experimental conditions Maintenance environment: temperature 25℃, humidity 60%.

[0100] Drying conditions: temperature 60°C, drying time 24 hours.

[0101] Test samples: Example 1 (standard optimization), Example 3 (high-strength optimization), Example 5 (low-temperature optimization); Comparative Example 2 (no dynamic network reinforcement system), Comparative Example 4 (aggregate particle size does not meet the requirements).

[0102] Test results of crack number and maximum crack length of different samples The material's crack resistance is closely related to the dynamic network reinforcement system and the optimized design of aggregate particle size. In Example 3, the number of cracks is the least, only 1.3, and the maximum crack length is only 1.2 mm, which is significantly better than the comparative sample. This shows the key role of the dynamic network reinforcement system in resisting drying shrinkage stress. PEG and PVA form a dense flexible support network in the hardened slurry through cross-linking of flexible molecular chains. This network structure can buffer the micro-stress generated during the hydration process and effectively absorb shrinkage stress during the drying stage, thereby avoiding the formation and expansion of cracks; Since the dynamic network reinforcement system was not introduced in Comparative Example 2, the number of cracks was as high as 7, and the maximum crack length was 4.3 mm, showing obvious shrinkage cracking. This was mainly due to the lack of flexible connection between particles. The uneven distribution of particles during the drying process led to stress concentration, which eventually caused the rapid expansion of cracks. The lack of a dynamic network reinforcement system resulted in poor mechanical flexibility of the slurry after hardening, making it difficult to resist drying shrinkage stress; For Comparative Example 4, in which the aggregate particle size design is unreasonable, the number of cracks and the maximum crack length are also significantly higher than those of Example 1 and Example 3. This shows that the stress concentration caused by large-size aggregate inside the material cannot be ignored. Stress concentration will weaken the overall crack resistance of the material, especially during the drying process, when stress is more likely to expand along the boundaries of large-size aggregates, eventually forming larger cracks. In the embodiment, the reasonable aggregate particle size design combined with the filling effect of nano-magnesium silicate forms a more uniform microstructure inside the material, effectively blocking the stress expansion path and improving the crack resistance. In comparison, the crack resistance of Example 5 is slightly inferior to that of Example 3, but is still much better than the comparative example. Although low-temperature curing can improve the strength uniformity in the initial stage of hardening, it fails to significantly enhance the flexibility of the material. The dynamic network and particle size optimization play a more significant role in resisting drying cracks. The test results fully prove that the technical solution of the present invention achieves a comprehensive improvement in the material's crack resistance by optimizing the dynamic network system and aggregate particle size design.

[0103] Experiment 5: Construction performance test Experimental procedures Sample preparation Slurry was prepared according to the formula of Example 1, Example 3, Example 5 and Comparative Example 2 and Comparative Example 5.

[0104] Each sample was stirred strictly according to its process conditions and allowed to stand for 1 minute to ensure that the bubbles in the slurry were fully released.

[0105] Initial setting time test Equipment: Use a standard Vicat initial setting time tester.

[0106] Operation process: Pour the slurry into a standard cylindrical mold (75mm in diameter and 40mm in height).

[0107] Every 5 minutes, a Vicat needle was inserted vertically into the slurry and the insertion depth was measured.

[0108] When the needle insertion depth is less than 2 mm, it is recorded as the initial setting time.

[0109] Flow leveling time test Equipment: Standard flowability test mold (50 mm in diameter, 50 mm in height).

[0110] Operation process: Pour the slurry into the mold and observe the natural spreading of the slurry after removing the mold.

[0111] The slurry flow diameter was recorded every 3 minutes until the flow diameter stopped changing, and the final time was recorded as the flow leveling time.

[0112] Experimental conditions Temperature: 25℃; Humidity: 60%.

[0113] Test samples: Example 1 (standard optimization), Example 3 (high-strength optimization), Example 5 (low-temperature optimization); Comparative Example 2 (no dynamic network reinforcement system), Comparative Example 5 (retarder removed).

[0114] Test results of construction performance of different samples Construction performance is an important indicator to measure the adaptability of slurry during on-site operation, especially the initial setting time and flow leveling time, which directly affect the construction efficiency and quality. From the data, the initial setting time of Example 3 is 37 minutes, and the flow leveling time is 12.3 minutes, which is excellent. It shows that the scientific ratio of the retarder and the synergistic effect of the dynamic network reinforcement system play a key role in optimizing the construction performance. The dynamic network reinforcement system provides flow stability through the flexibility of the molecular chain, and controls the dispersibility of the slurry, making it more uniform during the flow process, avoiding the loss of fluidity caused by early water loss; In Comparative Example 2, after the dynamic network reinforcement system was removed, the initial setting time was greatly shortened to only 15.3 minutes, while the flow leveling time was as high as 26 minutes. This result shows that the flow performance of the slurry is greatly reduced due to the lack of flexible connection and dispersed support between particles. Without the support structure of the dynamic network, the slurry coagulates rapidly in a short time, and the stability of the construction operation cannot be guaranteed. In Comparative Example 5 in which the retarder is removed, the initial setting time is only 11 minutes, which obviously cannot meet the construction requirements. At the same time, its flow and leveling time reaches 31 minutes, showing a serious construction delay problem. The retarder delays the hydration reaction rate of gypsum to ensure that the slurry maintains stable fluidity and viscosity during the operation stage, thereby avoiding quality problems caused by premature loss of fluidity during the construction process. The experimental results of Comparative Example 5 verify that the slurry without a retarder is obviously unstable during the operation window period and cannot meet the actual construction requirements. The construction performance of Example 1 and Example 3 is stable, which fully reflects the reasonable design of the retarder in the present invention, the uniform dispersion effect of the dynamic network reinforcement system, and the fluidity improvement effect of the hydrophobic modification of the aggregate. The optimization of these synergistic effects fundamentally solves the technical bottleneck of the poor construction performance of traditional gypsum self-leveling.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A dust-free lightweight gypsum self-leveling, characterized in that: The self-leveling gypsum comprises the following components in parts by weight: Gypsum base material: hemihydrate gypsum: 300-400 parts; α high-strength gypsum: 100-150 parts; Lightweight aggregate: vitrified microspheres: 150-200 parts; expanded perlite: 50-100 parts; Dynamic network enhancer: polyethylene glycol: 20-40 parts; Polyvinyl alcohol: 10-20 parts; Silane coupling agent: 5-10 parts; Interface regulator: nano magnesium silicate: 10-20 parts; hydrophobic modified silane: 5-10 parts; Fluidity regulator: polycarboxylate water reducer: 2-5 parts; thickener: 2-5 parts; Auxiliary additives: latex powder: 20-30 parts; white oil: 10-20 parts; retarder: 1-3 parts; defoaming agent: 1-3 parts; anti-cracking fiber: 0.5-1 part.

2. A dust-free lightweight gypsum self-leveling according to claim 1, characterized in that: The lightweight aggregate comprises: Vitrified microspheres, with a particle size of 10 to 150 microns; Expanded perlite, particle size 50 to 200 microns; The surfaces of the vitrified microspheres and expanded perlite are treated with hydrophobically modified silane and then dried for use.

3. The dust-free lightweight gypsum self-leveling according to claim 1, characterized in that: The dynamic network enhancer comprises: Polyethylene glycol, molecular weight 4000-6000; Polyvinyl alcohol, alcoholysis degree is 87% to 98%, and polymerization degree is 1700 to 2000; The silane coupling agent is KH-1720 silane.

4. The dust-free lightweight gypsum self-leveling according to claim 1, characterized in that: The interface regulator comprises: Nano magnesium silicate, particle size is 20-50 nanometers, specific surface area is 200-300m 2 / g; The amount of hydrophobically modified silane is 0.5% to 1% of the aggregate weight.

5. The dust-free lightweight gypsum self-leveling according to claim 1, characterized in that: The fluidity modifier includes: Polycarboxylic acid water reducer, the main chain structure is polyether type, the molecular weight is 20000-30000; Thickener, viscosity is 2000~4000mPa·s, particle size is less than 100 microns.

6. The dust-free lightweight gypsum self-leveling according to claim 1, characterized in that: The auxiliary additives include: Latex powder, particle size is 50 to 200 microns; White oil, which is No. 100 mineral oil; The retarder is sodium citrate; The defoaming agent is polyether modified silicone oil.

7. A method for preparing dust-free lightweight gypsum self-leveling, characterized in that: Using the dust-free lightweight gypsum self-leveling method according to any one of claims 1 to 6 comprises the following steps: S1. The aggregate is subjected to hydrophobic modification treatment to improve the bonding strength between the aggregate and the substrate; at the same time, the liquid phase additive is mixed and dissolved to form a uniformly distributed dynamic network reinforcement system; S2, adding the dry raw materials into a mixer and mixing to form a uniform dry blend; S3. Slowly add the liquid phase additive to the dry mix, and add latex powder and retarder at the same time to further enhance fluidity and construction adaptability; S4. Spray white oil through a spraying device during the stirring process to reduce dust and improve particle lubricity. The spraying pressure is 4-6 MPa and the spraying time is 3-5 minutes. S5. Spread the evenly stirred slurry onto the construction surface to fill the uneven surface and achieve a self-leveling effect. The initial setting time is 25 to 40 minutes. S6. Wet-cure the completed surface to ensure material strength and stability. The curing temperature is 20-30°C, the humidity is 50%-70%, and the curing time is 48 hours.

8. The method for preparing a dust-free lightweight gypsum self-leveling according to claim 7, characterized in that: The S1 includes: The vitrified microspheres and expanded perlite were subjected to hydrophobic modification using KH-560 silane at a modification temperature of 50-70°C for 2-4 hours; Dry the modified aggregate at a temperature of 50 to 60°C for 2 to 3 hours; Polyethylene glycol and polyvinyl alcohol are dissolved in warm water at a weight ratio of 1:1 to 2:1, the dissolution temperature is 50 to 60° C., and the stirring time is 5 to 10 minutes to prepare a uniform liquid phase mixture.

9. The method for preparing a dust-free lightweight gypsum self-leveling according to claim 7, characterized in that: The S2 includes: Add hemihydrate gypsum, α high-strength gypsum, vitrified microspheres, expanded perlite and nano magnesium silicate into a dry mixer according to proportion; The stirring speed is 200-500 rpm; The stirring time is 3 to 5 minutes; Control the uniform distribution of particles during mixing to avoid aggregate separation; After the dry mixing is completed, the mixture is left to stand for use in subsequent liquid phase mixing operations.

10. The method for preparing a dust-free lightweight gypsum self-leveling according to claim 7, characterized in that: The S3 includes: Slowly add the liquid mixture to the dry mix at a rate of 100-200 mL / min to prevent uneven mixing; While adding the liquid phase mixture, add the latex powder, retarder and defoamer in sequence; The stirring speed of wet mixing is 300-600 rpm, and the stirring time is 5-8 minutes; During the wet mixing process, white oil is sprayed through high-pressure spraying equipment with a spraying pressure of 4 to 6 MPa and a spraying time of 3 to 5 minutes to further reduce dust generation.